Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2019)
A dataset containing 94 species occurrences available in GBIF matching the query: { "and" : [ "Country is Uruguay", "TaxonKey is Otariidae" ] } The dataset includes 94 records from 9 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0006682-190813142620410/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences